Experimental study of windowpane’s atmospheric particulate accomulation on daylight transmition - Alizadeh, Asad; Yousif Ali, Diyar; Hossein Abadi, Amin Roostaee; Aminian, Saman; Lahonian, Mansour (Nexo Revista Científica, 2019)
Daylight is one of the most significant light source which could illuminate interior spaces by passing through windows and light collectors. Dust and aerosol accumulation on windowpanes reduce the light amount passing through it. The main objective of this research is to determine the impact of airborne particulate matters deposition on past light quantity. In this experiment the most prevalent particulate matters such as dust, carbon, and a mixture of both examined with 3 mm common commercial glasses at single and double glaze windowpanes and several interesting observations have been obtained. The result of this experiment will help building owners to adjust a window-cleaning schedule to reduce their lighting electricity consumption and expenses.